Il mondo slavo e l'Europa Contributi presentati al VI Congresso Italiano di Slavistica (Torino, 28-30 settembre 2016) - Bragone, Maria Cristina; Bidovec, Maria (Biblioteca di Studi Slavistici, 2019)
This volume, organised in thirty-two essays written by thirty-five among the most successful Italian scholars in the field of Slavic Studies, offers an extensive overview of the studies which have been conducted in Italy on Slavic literature, philology, linguistics, history and culture in recent years. Overall, the work highlights the great variety of paths and lines of research which shaped Italian Slavic Studies, and which are still being used for this field. This volume shows several realities of the Slavic countries in their multifaceted relations with other European cultures, and is addressed to researchers focusing only on Slavic Studies as well as to specialists from other fields who are interested in further investigating topics related to the close net of relationships between the Slavic world and the rest of Europe in the past and present.